Imaging and Diagnosis in Pediatric Brain Tumor Studies - Warmuth-Metz, Monika (Springer International Publishing : Imprint: Springer, 2017)
This book describes the features in structural imaging of the most important pediatric brain tumors with the aim of enabling radiologists to make the correct differential diagnosis and to provide the pediatric oncologist with all the imaging information relevant to further management. The opening chapter is devoted to the complex subject of pediatric trials at the national and international levels and the importance of staging for stratification, differential treatment, and outcome. A general imaging protocol for children with brain tumors is presented, and individual chapters then identify key points for the differential diagnosis and staging of posterior fossa tumors, low- and high-grade gliomas, germ cell tumors, and craniopharyngiomas. The relevance of aspects such as tumor site and age to diagnosis is explained, and pitfalls associated with meningeal dissemination and treatment-related complications mimicking recurrence are highlighted. The importance of ensuring comparability of follow-up by use of standard MR (or CT) imaging is emphasized. In drawing on the lessons gained both from pediatric trials and from the author's own experience, this book will be invaluable for all radiologists.